Comprehensive analysis to identify a novel PTEN-associated ceRNA regulatory network as a prognostic biomarker for lung adenocarcinoma - Xin, Rui; Shen, Biao; Jiang, Ying-Jie; Liu, Ji-Bin; Li, Sha; Hou, Li-Kun; Wu, Wei; Jia, Cheng-You; Wu, Chun-Yan; Fu, Da; Ma, Yu-Shui; Jiang, Geng-Xi (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) is one of the most prevalent forms of lung cancer. Competitive endogenous RNA (ceRNA) plays an important role in the pathogenesis of lung cancer. Phosphatase and tensin homolog (PTEN) is one of the most frequently deleted tumour suppressor genes in LUAD. The present study aimed to identify a novel PTEN-associated-ceRNA regulatory network and identify potential prognostic markers associated with LUAD. Transcriptome sequencing profiles of 533 patients with LUAD were obtained from TCGA database, and differentially expressed genes (DEGs) were screened in LUAD samples with PTEN high- (PTENhigh) and low- (PTENlow) expression. Eventually, an important PTEN-related marker was identified, namely, the LINC00460/miR-150-3p axis. Furthermore, the predicted target genes (EME1/HNRNPAB/PLAUR/SEMA3A) were closely related to survival and prognosis. The LINC00460/miR-150-3p axis was identified as a clinical prognostic factor through Cox regression analysis. Methylation analyses suggested that abnormal regulation of predicted target genes might be caused by hypomethylation. Furthermore, immune infiltration analysis showed that the LINC00460/miR-150-3p axis could alter the levels of immune infiltration in the tumour immune microenvironment and promote the clinical progression of LUAD. To specifically induce PTEN deletion in the lungs, we constructed an STP mouse model (SFTPC-rtTA/tetO-cre/Ptenflox/+). Quantitative PCR (qPCR) and immunohistochemical (IHC) analysis were used to detect predicted target genes. Therefore, we revealed that the PTEN-related LINC00460/miR-150-3p axis based on ceRNA mechanisms plays an important role in the development of LUAD and provides a new direction and theoretical basis for its targeted therapy.